MORPHOLOGICAL CHANGES OF THE SKIN IN A POSTOPERATIVE WOUND AT THE SYNDROME OF OPIOID-INDUCED HYPERALGESIA - Dmytriiev, D. V. (Journal of Education, Health and Sport, 2015)
Dmytriiev D. V. Morphological changes of the skin in a postoperative wound at the syndrome of opioid-induced hyperalgesia. Journal of Education, Health and Sport. 2015;5(12):262-270. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35417 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A262-270 http://pbn.nauka.gov.pl/works/681494 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 14.12.2015. Morphological changes of the skin in a postoperative wound at the syndrome of opioid-induced hyperalgesia D. V. Dmytriiev Vinnytsya National Pirogov Memorial Medical University Department of anesthesiology and intensive care Resume The article describes the morphological changes of the skin in the area of postoperative wound. It has been found that the use of high doses of fentanyl (10-20 mcg/kg/hr) by continuous infusion for analgesia in the early postoperative period in children operated on for tumors of abdominal cavity can cause opioid-induced hyperalgesia, which is accompanied by morphological changes in the skin around the postoperative wound with the development of necrosis in the center of it, with expressed perifocal reactive changes in the form of significant inflammation and violations of microcirculation with the formation of the small nerve fibers on the 14th day. There was fibrosis of the derma with the formation of large amount of collagen fibers with their edema and lamination. Key words: analgesia, hyperalgesia, skin biopsy.